Pengaruh Citra Merek Dan Kualitas Produk Terhadap Kepoutusan Pembelian Minuman Teh Dalam Kemasan Siap Saji Teh Botol Sosro - Prasetya, Ma’ruf Akbar; Harwani, Yuli (Teropong : Jurnal Manajemen dan Bisnis, 2021)
This study aims to to examine and analyze the influence of image brands and product quality of the decision the purchase drink tea in packs brand tea bottles sosro in indonesia. (a case study on the consumer they get milk to drink a small plastic bottle full of tea leaves are set sosro in kecamatan kebon jeruk , west jakarta). Technique the sample collection in this research the convenience of sampling. Respondents in this research as many as 100 respondents from the customers tea in sub-district kebon jeruk sosro bottle , west jakarta. It is an approach that in use on of this research is structural equation a model (shem) with a tool it is anticipated that analysis smart-pls. The results of the test which has been these chareges in the future after do our tests structural models such as linking banks/efforts whatever survives this test a hypothesis (inner religion a model) shows that brand shots would take off and the product quality and increase of the decision of pt indofood acquired misp shares. Variable image brand have had a positive impact and significant of the decision the purchase. The product quality variable have had a positive impact and significant of the decision of the purchase.